Exploring Internet Financial Reporting (IFR) strategies of firms in Malaysia / Kamarul Baraini Keliwon ... [et al.] - Keliwon, Kamarul Baraini; Abdul Shukor, Zaleha; Muhammadun Mohamed, Zakiah; Hassan, Mohammat Sabri (Accounting Research Institute & Faculty of Accountancy, 2014)
Most firms currently utilise Internet financial reporting (IFR) because the Internet offers a more flexible presentation and content of reporting as well as allows the disclosure of more information. However, researchers argue that firms have to adopt corporate disclosure strategies to benefit from such innovations in technology. By using the taxonomy of Williams (2008), this study aims to investigate the IFR disclosure strategies that are being used by publicly listed firms in Malaysia. A detailed content analysis of the IFR disclosures of two firms reveals that both firms adopt different types of IFR disclosure strategies even if they are in the same industry. This finding provides preliminary evidence on the possibility for firms to utilise multiple IFR disclosure strategies. The findings from this study can also help stakeholders understand the IFR disclosure strategies that are possibly employed by firms, which can subsequently help them in making decisions.